Does Entitlement Card ensure Utilization of Urban Primary Healthcare Clinic in Bangladesh? - Sharmin, Mizan; Md Mizanur, Rahman; Razitasham, Safii; Sk Akhtar, Ahmad (2020)
Background:Although Bangladesh substantial-ly reduced 40% maternal death in the last deca-des, it is still challenging, especially among the urban poor. The achievements are not equitable between different economic quintiles and bet-ween the rich and the urban poor. This study aims to examine the extent to which the entitle-ment card affects the utilizationof maternal and child health care and identifies other factors that influence MCH services.Subjects and Method:This cross-sectional study was carried out in the working areas of the Urban Primary Healthcare Project (UPHCP) in Bangladesh. A two-stage cluster sampling techni-que was used to select the participants. Atotal of3,949 women aged 15-49 years, having at least one child aged two years or lesswere selected for this study. The data were collected through face-to-face interviews. The data were analyzed using multinomial logistic regression.Results:The proportion of utilizationof UPHCC was 49.9%. One-fourth (26.6%) of them fully utilized it and another 23.3% utilized it partially. Stepwise multinomial logistic regression analysis revealed that those who had an Entitlement Card from the UPHC project were 11.75 times (95% CI= 9.481, 14.549; p= 0.001) more likely to fully Utilized and 3.64 times (95% CI= 3.643, 2.911; p= 0.001) likely be utilized partially compared to non-utilizer. Respondents having no formal edu-cation utilized UPHCC fully (AOR=2.32; 95% CI= 1.46, 3.68; p= 0.001) and partially (AOR=1.76; 95% CI= 1.12, 2.77; p= 0.014) used UPHCC. It was 3.08 (95% CI= 2.03, 4.67; p= 0.001) times for fully and 2.71 (95% CI= 1.82, 4.04;p= 0.001) times for partially utilized UPHCC compared to non-users among the primary level of education. Small family size (≤4) and monthly family in-come in the range of BDT 10,000 above were likely to utilise UPHCC. However, non-Muslims were less likelyto Utilized UPHCC.Conclusion:Apart from the entitlement card, other factors such as monthly income BDT>10,000, small family size, no formal educated mother appeared to be potential predictors for utilizationof the Urban Primary Health care clinic.